2010
DOI: 10.1093/hmg/ddq531
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetics of neurons inhibit the translocation response of Parkin following rapid mitochondrial depolarization

Abstract: Recent studies delineate a pathway involving familial Parkinson's disease (PD)-related proteins PINK1 and Parkin, in which PINK1-dependent mitochondrial accumulation of Parkin targets depolarized mitochondria towards degradation through mitophagy. The pathway has been primarily characterized in cells less dependent on mitochondria for energy production than neurons. Here we report that in neurons, unlike other cells, mitochondrial depolarization by carbonyl cyanide m-chlorophenyl hydrazone did not induce Parki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
185
7
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(208 citation statements)
references
References 45 publications
15
185
7
1
Order By: Relevance
“…In fact, it has been reported that unlike other cell types, depolarization of neuronal mitochondria does not lead to Parkin recruitment or their autophagic clearance. 102 On the other hand, recruitment of Parkin to depolarized neuronal mitochondria and their Parkin-dependent mitophagy have been observed in other studies. 69,86 Clearly, further work is required to address the relevance of the PINK1/Parkin-mediated pathway of mitophagy in neurons.…”
Section: Mitophagy In Neuronsmentioning
confidence: 75%
“…In fact, it has been reported that unlike other cell types, depolarization of neuronal mitochondria does not lead to Parkin recruitment or their autophagic clearance. 102 On the other hand, recruitment of Parkin to depolarized neuronal mitochondria and their Parkin-dependent mitophagy have been observed in other studies. 69,86 Clearly, further work is required to address the relevance of the PINK1/Parkin-mediated pathway of mitophagy in neurons.…”
Section: Mitophagy In Neuronsmentioning
confidence: 75%
“…Thus, stabilization of Pink1 at the OM and recruitment of Parkin to the mitochondrial OM is crucial to induce mitophagy Chan et al 2011). It will be interesting to define the contribution of blocked OM protein degradation and mitophagy to the progression of Parkinson's disease, especially with the recent observation that Parkin does not appear to be recruited to mitochondria in neuronal cells (Van Laar et al 2011).…”
Section: Parl Processes Pink1 Within Mitochondriamentioning
confidence: 99%
“…Mitochondrial Depolarization-induced Parkin Mitochondrial Recruitment and Elevated PINK1 Levels Correlate with Intracellular ATP Levels-Previous studies have shown that the rapid loss of ATP after mitochondrial depolarization could be one of the reasons behind poor Parkin-mitochondrial translocation in neurons or HeLa cells forced into dependence on mitochondrial respiration (24). Because HeLa cells and immortalized cell lines generally utilize glycolytic metabolism for energy production, it is our expectation that glucose withdrawal coupled with mitochondrial depolarization would severely suppress intracellular ATP levels.…”
Section: Glucose Is Required For Cccp-induced Mitophagic Response-mentioning
confidence: 99%
“…Although several studies have verified this observation in neuronally derived (4,23) and non-neuronal immortalized cell lines (2,4,5), the PINK1/Parkin mitophagy pathway has been proven to be less robust in neurons (24). To date, research in this field predominantly relied on ionophores and inhibitor drugs to compromise the mitochondrial integrity (3,(25)(26)(27).…”
mentioning
confidence: 99%
See 1 more Smart Citation